Analysis of the characteristics of the spectral orthogonal decomposed flow fields: Numerical and experimental investigations of the air flow field around a simplified container ship model. (15th December 2022) - Deng, Rui; Wang, Yu-quan; Song, Zhi-jie; Li, Hao; Wu, Tie-cheng
Abstract: The instability of the wind resistance on container ships with a certain windward area often depends on the shedding of vortices on the surface of the hull. This affects the navigation of the ship. However, the flow field around the container ship is composed of lots of modes of different frequencies and energy, only some of them have close relationship with energy saving. In order to investigate the characteristics of the flow motions necessary, three-dimensional flow field around the container ship is simulated by Large Eddy Simulation(LES) and validated by model test. Then the two-dimensional simplified container ship model is adopted to highlight the characteristics of the flow field, the Reynolds number of the flow field analyzed at this time is 2 . 53 × 1 0 6 . The flow field around the two-dimensional model is simulated and decomposed by spectral proper orthogonal decomposition (SPOD), it is found that the Strouhal numbers of vortex shedding obtained by λ 2 criterion and vorticity method is consistent with that calculated by SPOD. The energy of the flow motion related to the present study is dominated by the primary flow structure decomposed by SPOD, and the high frequency motion obtained by SPOD has little contribution on it. An in-depth analysis of the flow field is performed in the present investigation by taking the flow field around a container ship for example, the further study of the three-dimensional problem is also expected. Highlights: The energy attenuation between modes is regular, which is almost no crossover. The coherent flow structure is consistent with the macroscopic flow field. The macroscopic frequency of the vortex is determined by main vortex structure.